Ethnic Comparisons of Spike-Specific CD4+ T Cells, Serological Responses, and Neutralizing Antibody Titers Against SARS-CoV-2 Variants - Fani Pantouli; Vanessa Silva-Moraes; Ted M. Ross (Vaccines)
Background/Objectives: To evaluate how immune responses compare among ethnic groups approximately 2 years after receiving a third dose of COVID-19 vaccine (BNT162b2, mRNA-1273, ChAdOx1or BBIBP-CorV), we tested T cell responses and Spike-specific RBD-antibody titer, and neutralized antibody titer levels utilizing Spectral Flow cytometry, ELISA, and SARS-CoV-2 pseudotyped-based neutralization assays, respectively. Methods: Forty-four individuals from January–December 2023 were identified within the cohort and were classified into different ethnic backgrounds; Black (N = 13), Asian (N = 14), Caucasian (N = 17). We recognize that the “Asian” group includes diverse subpopulations with distinct genetic and environmental backgrounds, which could not be further stratified due to sample-size limitations. Spike-specific AIM+, CD4+, and CD8+ T cell responses were assessed and evaluated against SARS-CoV-2 variants, including the ancestral Wuhan, Delta, and multiple Omicron subvariants (B1.1529, BA2.86, BA.4/5, and XBB.1). Alongside we tested the RBD-IgG and neutralizing antibody titers against the ancestral Wuhan. Spearman’s correlation analysis was utilized to determine corelative relationships among the AIM+ and CD4+ T cell responses, as well as the RBD-IgG and neutralizing antibody titers. Results: Our results show robust and comparable RBD-IgG and neutralizing antibody titers across all groups, with a significant positive correlation between these two measurements. Significant differences were observed in T-cell activation, with Asian participants exhibiting lower frequencies of Spike-specific CD4+ T cells against SARS-CoV-2 Omicron subvariants and higher frequencies of cytokine-producing CD4+ T cells (TNF-α, IFN-γ, and IL-2) as compared to the Caucasian group. Breakthrough infection status was not fully controlled and may influence these findings. Conclusion: Despite a small sample size and potential confounding by natural infections within our long-time-span sampling, our data suggest persistent cellular and humoral immunity 2 years after vaccination across ethnicities, with notable differences in T cell activation and cytokine profile. These preliminary observations highlight the need for larger, more detailed studies that consider intra-ethnic diversity and hybrid immunity to better understand ethnic differences in COVID-19 vaccine responses.